IoT-Based Diabetes Management: Advancements and Challenges in Healthcare - Ram Parab; Omkar Sawant (International Journal of Optical Innovations & Research, 2025)
The integration of the Internet of Things (IoT) into healthcare has revolutionized disease management by enabling real-time monitoring, data analysis, and proactive interventions. This paper explores how IoT applications can significantly enhance diabetes management by providing sustainable and innovative healthcare solutions. Leveraging IoT-enabled devices such as Continuous Glucose Monitoring (CGM) systems, smart wearables, and remote patient monitoring tools, diabetes care can be personalized and made more efficient, reducing long-term complications. The study emphasizes the role of IoT in supporting self-management, reducing dependency on physical consultations, and minimizing environmental and economic costs through smarter healthcare systems. Despite the transformative potential, challenges such as data privacy, security, and interoperability persist. This paper presents a comprehensive review of IoT applications for diabetes management, underlining their importance in achieving sustainable healthcare goals in Viksit Bharat.
Keywords: IOT; Internet of Things; diabetes management; healthcare sustainability; smart healthcare systems